INFORMATION STRUCTURE AND WORD ORDER VARIATIONS (Journal of Contemporary Philology, 2021)
This paper aims to determine the effects of information structure (IS) on word order in standard Macedonian. We classify and describe the linearization patterns of simple sentences according to their communicative goal. The classification is based on the discourse-semantic distinction between categorical and thetic utterances. Sentences that function as categorical judgments typically predicate some property of a contextually known subject referent. Hence they have а binary topic-comment IS reflected in prosody and unmarked SV word order. In contrast, thetic utterances do not predicate a property but introduce a new participant into the discourse (presentative constructions) or report the occurrence of an event. This means that their IS consists only of a focus part, which tends to be marked by subject-predicate inversion. It is presumed that an implicit circumstantial locative or temporal adjunct serves as their stage topic. However, its realization in a sentence-initial position imposes a binary topic-comment IS in presentative sentences, triggering an obligatory subject-predicate inversion.
Keywords: categorical and thetic utterances; inversion; presentative constructions; stage topic